Rancang Bangun Alat Kontrol Operasional Pompa Air pada Dua Pemakai Skala Rumah Tangga - Tanda Saputra; Muhammad Hafidz; Muhammad Fajrian Akbar; Bastaman Syah; Yose Sabastian (Jurusan Teknologi Pertanian, 2015)
Indonesia still through water scarcity, ironicaly Indonesia included in 10 countries with rich sources of fresh water.Â In urban areas generally people can get fresh water source from water pump with making an artesian well or deep well. Artesian well water pump is very expensiveif itâ€™s used only in one house.Â To make efficient, using one pump for two or more houses can be overcome by making â€œoperational control device pumps waterâ€.Â Utilizing the interlock system used on two houses and one well, so if one house pump turned on, another house canâ€™t be turned on an off except after reservoir tank fulled of water, another house can be turned on the water pump. Reservoir tank is used automatically by using a ball floater switches.Â When the water in the reservoir tank is full, the pump doesnâ€™t work so that water is not wasted in vain. This tool design cane save half the cost compared to each house makes its own borehole and pump water, because the system is supplied electrical energy to the water pump from each house.Â Keywords: water pump, artesian well, interlock, reservoir tank automatic